Situational analysis of services for diabetes and diabetic retinopathy and evaluation of programs for the detection and treatment of diabetic retinopathy in India: Methods for the India 11-city 9-state study - Murthy, G. V. S. (Indian J Endocrinol Metab, 2016)
BACKGROUND: Diabetic retinopathy (DR) is a leading cause of visual impairment in India. Available evidence shows that there are more than 60 million persons with diabetes in India and that the number will increase to more than a 100 million by 2030. There is a paucity of data on the perceptions and practices of persons with diabetes and the available infrastructure and uptake of services for DR in India. OBJECTIVES: Assess perception of care and challenges faced in availing eye care services among persons with diabetics and generate evidence on available human resources, infrastructure, and service utilization for DR in India. METHODS: The cross-sectional, hospital-based survey was conducted in eleven cities across 9 States in India. In each city, public and private providers of eye-care were identified. Both multispecialty and standalone facilities were included. Specially designed semi-open ended questionnaires were administered to the clients. Semi-structured interviews were administered to the service providers (both diabetic care physicians and eye care teams) and observational checklists were used to record findings of the assessment of facilities conducted by a dedicated team of research staff. RESULTS: A total of 859 units were included in this study. This included 86 eye care and 73 diabetic care facilities, 376 persons with diabetes interviewed in the eye clinics and 288 persons with diabetes interviewed in the diabetic care facilities. CONCLUSIONS: The findings will have significant implications for the organization of services for persons with diabetes in India.